THE ROLE OF TECHNOLOGY IN EDUCATIONAL SCIENTIFIC WORKS: A LITERATURE REVIEW AND EDUCATIONAL IMPLICATIONS - Usman, Misnawaty; Nurjanna, Rifda; Adys, Himala Praptami; Adys, Himaya Praptani (JOURNAL OF HUMANITIES AND SOCIAL STUDIES, 2024)
The rapid evolution of Information and Communication Technology (ICT) has profoundly influenced multiple sectors of society, with education being no exception. Educational scientific works, as critical outputs of scholarly inquiry, are increasingly shaped by technological advancements. These developments have created novel opportunities in the areas of research design, data collection, analysis, and the dissemination of findings. This paper seeks to explore the role of technology in the context of educational scientific works through a comprehensive literature review. The review synthesizes various scholarly sources addressing the integration of technology in educational research, focusing on methodological approaches, data gathering techniques, data analysis processes, and the dissemination of research outcomes. Additionally, this study identifies the practical implications of technological adoption for the advancement of educational scientific works, highlighting its contributions to improving research efficiency, accuracy, and scope. Moreover, the use of technology facilitates enhanced collaboration and provides expanded access to educational resources, promoting a more inclusive learning environment. The findings suggest that technology not only enhances the quality and relevance of educational research but also opens new pathways for the development of knowledge and the transformation of educational practices in the digital era. Keywords: Information and Communication Technology, Educational Scientific Works, Literature Review, Research Methodology, Practical Implications.